The use of artificial substrate and materials for nest building in 2 ground-finches (Geospiza spp.) under human-altered conditions - Gutiérrez Vannucchi, Ana Cecilia (2021)
Urbanization is one of the main problems for biodiversity around the world, associated with a decrease of natural habitats and its resources. In contrast, urbanization can also provide new resources that could be used by species that thrive in cities. Understanding why this happens is basic to understand species adaptation to urban areas. Here, we report a nest of a Medium Ground-Finch (Geospiza fortis) built inside a C-purlin beam and artificial materials used for nest building by Medium and Small (G. fuliginosa) ground-finches. The changes that can be observed in some populated areas of the Galapagos Islands, where land cover has been transformed from native habitats into farms, plantations, and urban areas, provide new resources and challenges for native birds and other animals. We discuss the advantages and disadvantages of using artificial materials in nest building and how this may help birds survive in urbanized areas.